PELATIHAN KELEMBAGAAN DAN DINAMIKA KELOMPOK PADA KELOMPOK TANI DAN USAHA PERDAGANGAN DI DESA SIDAN, KABUPATEN GIANYAR - I Gede Aryana Mahayasa; Ida Ayu Putu Widani Sugianingrat; Pande Nyoman Santi Ardani; Wayan Andhika Putrayasa (UNHI Press, 2022)
The institutional aspect emphasizes the order of moral values, patterns of human relations, and the regulations that apply in society. Organizational or institutional structure is defined as how a job has been divided, grouped or formally coordinated. Group dynamics as a method and process, is one of the management tools to produce optimal group collaboration, so that organizational management becomes more effective, efficient and productive. Group dynamics seeks to create situations in such a way that all group members feel actively involved in each stage of group development or growth, so that everyone feels part of the group and not a stranger. This community service activity is carried out in order to help the community, especially farmer groups, a combination of farmer groups and trading business groups in Sidan village, Gianyar to be able to understand more about the organization, institutional or organizational structure and group dynamics within the organization. After attending this training, it is hoped that these business groups will be better able to organize and manage their organizations and could manage the dynamics that occur in their organizations, so that they can be optimized to achieve their organizational goals.